PEMBERDAYAAN EKONOMI PEREMPUAN KELOMPOK WANITA NELAYAN KOTA MAKASSAR (STUDI KASUS KWN FATIMAH AZ-ZAHRA) - Muchlis, Nurannisa Sri Febriani; Kamaruddin, Citra Ayni; Rajab, Abdul; Astuty, Sri (Bisnis-Net, 2025)
Currently, women's empowerment is a very important global issue and contributes to sustainable socio-economic development. This empowerment is carried out to increase the capacity of the community, especially women, so that they can achieve a better quality of life. The aim of this research is to determine the effectiveness of the women's economic empowerment program on the income level of KWN Fatimah Az-Zahra members in Pattingalloang District, Makassar City. Quantitative Descriptive research method with a total sample of 72 respondents. The results of the research show that the Women's Economic Empowerment Program has a significant impact on the income level of members of the Fatimah Az-Zahra Women Fishermen Group, this results in the hypothesis being accepted.  So the result to answer the problem formulation is that the Women's Economic Empowerment Program on the Income Level of KWN Fatimah Az-Zahra Members in Pattingalloang Subdistrict, Makassar City is Effective with an Effectiveness Level of 88%.